Solid state reactions in the platinum-mercury system - Souza, G. R.; Pastre, I. A.; Benedetti, Assis Vicente [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Fertonani, F. L. (Springer, 2007)
Thermogravimetry, Differential Scanning Calorimetry and other analytical techniques (Energy Dispersive X-ray Analysis; Scanning Electron Microscopy; Mapping Surface; X-ray Diffraction; Inductively Coupled Plasma Atomic Emission Spectroscopy and Cold Vapor Generation Atomic Absorption Spectroscopy) have been used to study the reaction of mercury with platinum foils. The results suggest that, when heated, the electrodeposited Hg film reacts with Pt to form intermetallic compounds each having a different stability, indicated by at least three mass loss steps. Intermetallic compounds such as PtHg4, PtHg and PtHg2 were characterized by XRD. These intermetallic compounds were the main products formed on the surface of the samples after partial removal of bulk mercury via thermal desorption. The Pt(Hg) solid solution formation caused great surface instability, attributed to the atomic size factor between Hg and Pt, facilitating the acid solution's attack to the surface.
Keywords: DSC; intermetallic compounds; mercury; platinum; TG; XRD